Fatores de riscos para doenças cardiovasculares em pacientes em um pronto atendimento - Fantini, Joseli Ferreira Angelini (2015)
Introduction: Cardiovascular diseases (CVD) affect a significant portion of Brazilians, accounting for 32% of deaths. The risk factors for CVD are varied and may be modified, such as hyperlipidemia, smoking, alcoholism, obesity, diabetes mellitus, hypertension, use of contraceptives, sedentary lifestyle, unbalanced diet and not modifiable, such as age, gender, ethnicity, family history cardiovascular disease. Among the CVD chest pain stands out and can be benign (musculoskeletal) or malignant as acute coronary syndromes (ACS), pulmonary embolism (PE), aortic dissection, pericarditis, pneumothorax, and esophageal perforation. The evaluation of patients with chest pain should focus on symptoms of SCA as myocardial infarction, stroke, heart failure, recurrent symptoms of severe arrhythmias or ischemia. A proper investigation and treatment based on protocols are significant tools in the survival of patients with cardiovascular disease. Objetives: Demographically characterize patients treated with cardiovascular disease in an emergency service NHS and private; identify risk factors for cardiovascular disease in these patients and check the destination. Method: cross-sectional survey of electronic medical record analysis of treated patients in the emergency room with cardiovascular disease, and the sample consists of a total of 4920 patients. For data analysis, we used descriptive analysis of the variables of the sample characterization and risk factors; Chi-square test, analysis of variance (ANOVA) with multiple comparison test of Tukey at P <0.05. Results: The results show that most of the patients were male (50.38%), with basic education (53.45%), with a partner (63.25%), service sector workers (34.99 %), white, with a median age of 54 years. The main reason for attendance was the chest pain and the main risk factor found was hypertension. Regarding the fate of patients, most patients discharged presented chest pain, hospitalized patients had mostly angina and patients who died, mostly presented infarction. Conclusion: It is of great importance to effective community participation in prevention and health promotion programs, which would reduce the levels of risk factors and, consequently, the percentage of cardiovascular disease.